Knowledge, Awareness, and Practices among Pakistani Population regarding COVID-19: An Online Survey-Based Study - Uzair, Mohammad; Farooq, Ahmad; Arshad, Muhammad; Waheed, Usman; Ullah, Rana Hissan; Bashir, Shahid (Ibnosina Journal of Medicine and Biomedical Sciences, 2022)
Aim The study aims to analyze the knowledge, awareness, and practices among the Pakistani population.Study Method This is an online survey-based study conducted in July 2020 among the general public of Pakistan. Pretested and structured self-administered questionnaire, designed on Google Forms Inc., was used to collect data. The questionnaire included sociodemographic and measurable coronavirus disease 2019 (COVID-19) knowledge data. Assessments on participants' attitudes and practices toward COVID-19 included questions on transmission, symptoms knowledge, and preventive measures.Results Among the survey completers (n = 962) 61% (n = 590) were male and 39% (n = 372) were female. The majority of participants is aged 18 to 25 and belonged to Punjab. The participants had moderate knowledge regarding disease origin, clinical features, symptoms, and prevention. A vast majority of participants had good knowledge of symptoms and prevention measurements. A good number of participants were also practicing precautionary measures. The majority of participants utilize media and government authorities as authoritative sources of information. The population was also satisfied with the information given by the government.Conclusion Participants have moderate knowledge regarding the COVID-19 pandemic, reflected by a positive attitude and safe practices. There are gaps in knowledge of the virus, its origin, and transmission. Rumors affect the psychology of people, which may lead to the worst situation of panic conditions.
Keywords: COVID-19; SARS-CoV-2; knowledge; prevention; public awareness